The Challenges Of Teachers In Teaching And Learning Process For Early Malay Reading Skills In Malaysian Primary School - Kamal, Nurfara Syakila Binti Samsul; A. Ghani, Muhammad Faizal (International Research-Based Education Journal, 2025)
Education is critical in the formation of a develop nation. Language literacy is a fundamental ability that students must master in order to help them have a good quality learning. This study aims to explore the challenges faced by the teachers in teaching and learning process for the students who is weak in Malay Literacy in primary school. This study was conducted as a case study using qualitative approach. The data collection is conducted through semi-structured interviews. A total of 4 teachers were selected as a respondents. The interview data was analyzed using thematic analysis. The result from the interviews found there is a need to develop a malay literacy teaching management module. The study found 6 themes of challenges that faced by the teachers which is student learning capabilities, classroom management, teaching aids, student behavior, and also parent behavior. The implication of this study is can assist teachers in planning and implementing quality learning and teaching